Food and nutrients in disease management - Kohlstadt, Ingrid (CRC Press, 2009)
Food and nutrients are the original medicine and the shoulders on which modern medicine stands. This title equips clinicians with the information they need to utilize nutritional medicine by enabling them to adjust medication dosage with diet, diagnose and correct nutrient deficiencies, and counsel patients on food selection.